Moderation of Perceived Usefulness and Ease of Online Learning Media on the Influence of Predictor Variables on Students' Level of Understanding - Agung Kresnandra, Anak Agung Ngurah; Anggara, I Wayan Gde Wahyu Purna (E-Jurnal Akuntansi, 2024)
This study aims to determine the moderation ability of perceptions of the usefulness and convenience of online learning media on the influence of student computer anxiety on the level of understanding of accounting. To achieve the research objectives, primary data was collected through the distribution of questionnaires (which have passed the validity and reliability tests of the instrument) on samples determined by the purposive sampling method, namely selecting samples by determining specific characteristics that are in accordance with research objectives so that it is expected to be able to answer research problems. . The data collected was first tested for compliance with the classical assumption requirements, then analyzed using the Moderation Regression Analysis (MRA) technique. The results of this study are that computer anxiety has a negative effect on the level of student understanding, interest in   learning has a positive effect on the level of student understanding, perceptions of usefulness and convenience do not moderate the effect of   computer anxiety on the level of student understanding, perceived usefulness moderates the effect of interest in learning on the level of student understanding, and perceived ease does not moderate the effect of interest in learning on the level of student understanding.